2012
DOI: 10.1002/bdrc.21021
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term Effects of Prenatal Stress and Glucocorticoid Exposure

Abstract: There is a growing body of evidence suggesting that events during prenatal life can have long-lasting effects on development and adult health. Stress during pregnancy is common and has been linked to increased incidence of a range of affective and behavioral outcomes in the offspring in later life and also some somatic outcomes. Glucocorticoids, and their actions on the fetus, which are regulated by placental 11β-hydroxysteroid dehydrogenase type 2 (11β-HSD2), are hypothesized to mediate these effects. Animal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 90 publications
2
27
0
Order By: Relevance
“…These observations are in agreement with studies in rabbits showing that reductions in maternal body weight can result in lowered fetal weight and transient alterations in ossification, representing a delay in development associated with growth retardation [37]. Also, food shortage generally increases baseline glucocorticoids [40,41] and in mammals' cortisol passing the placental barrier is considered a primary origin of prenatal stress [41]. Hence, it can be hypothesized that a change in feeding regime or body weight gain may influence DI and result in higher FA levels and/or fPD through the action of glucocorticoids.…”
Section: Discussionsupporting
confidence: 90%
“…These observations are in agreement with studies in rabbits showing that reductions in maternal body weight can result in lowered fetal weight and transient alterations in ossification, representing a delay in development associated with growth retardation [37]. Also, food shortage generally increases baseline glucocorticoids [40,41] and in mammals' cortisol passing the placental barrier is considered a primary origin of prenatal stress [41]. Hence, it can be hypothesized that a change in feeding regime or body weight gain may influence DI and result in higher FA levels and/or fPD through the action of glucocorticoids.…”
Section: Discussionsupporting
confidence: 90%
“…Long-term effects seem to emerge not only after negative maternal behaviours, such as poor prenatal nutrition, but also following external, psychological and environmental stress in mothers (reviewed in Graham et al 2006). For example, early life stress through the excess of maternal stress hormones, mainly GC (Painter et al 2012), has been shown to relate to emotional problems and learning deficits, and it could lead to conditions such as type 2 diabetes and general depression and anxiety symptoms in adulthood (Weinstock 2008).…”
Section: Ageing Stress and The Immune Systemmentioning
confidence: 99%
“…Although glucocorticoids are essential for normal brain development, exposure of the fetal brain to an excess of glucocorticoids can also modify fetal brain development and permanently alter the function of the hypothalamic pituitary adrenal axis (HPA) in postnatal life [23][24][25]. There is evidence suggesting that events during prenatal life have longlasting effects during postnatal development and in the adult, for example altering the regulation of the HPA, increasing blood pressure and/or impairing glucose tolerance in the brain [26]. Indeed, it is known that prenatal glucocorticoids enhance the vulnerability to environmental toxicants [27] and furthermore, in the fetus glucocorticoids are thought to affect a range of affective and behavioral outcomes in the offspring in later life, as well as producing some somatic outcomes [26].…”
Section: Introductionmentioning
confidence: 98%
“…There is evidence suggesting that events during prenatal life have longlasting effects during postnatal development and in the adult, for example altering the regulation of the HPA, increasing blood pressure and/or impairing glucose tolerance in the brain [26]. Indeed, it is known that prenatal glucocorticoids enhance the vulnerability to environmental toxicants [27] and furthermore, in the fetus glucocorticoids are thought to affect a range of affective and behavioral outcomes in the offspring in later life, as well as producing some somatic outcomes [26].…”
Section: Introductionmentioning
confidence: 99%